PSXIV-7 Red blood cells are a better indicator than plasma for predicting subcutaneous trans fatty acid composition in cattle. (5th December 2019) - Dugan, Michael; Rolland, David; Block, Hushton; Vahmani, Payam
Abstract: The trans (t)-18:1 in beef has become of interest as partially-hydrogenated-vegetable-oils are removed from the food supply. Predicting t-18:1 in beef early in the feeding period would be useful if limitations are put on t18:1 in beef. The objective of the present study was to determine which blood component is a better predictor of t18:1 in beef. Accordingly, proportions of t10-18:1 and t11-18:1 (i.e. major t-18:1 isomers) were measured in heifer red blood cells (RBC) and plasma (2 pens of 7 animals) after 0, 28, 56 and 76d on a barley-grain-based diet, and also correlated with post-slaughter subcutaneous fat. Blood components were subjected to direct base then acid methylation, and subcutaneous fat to base methylation after freeze drying. c10-17:1 methyl ester was included as an internal standard. Fatty acid methyl esters were purified using Superclean LC-SI-SPE TM and then analyzed by GC using a 100m CP-Sil88 column. Fatty acids were analyzed using the Mixed Models procedure of SAS (v 9.3; SAS Institute, Cary, IN) with time as a repeated measure, and pen as a random factor. Pearson correlation coefficients were generated using the PROC CORR procedure of SAS. Proportions of total t-18:1 declined in both RBC and plasma during later stages of finishing (P < 0.05). At 28d, t11-18:1 decreased and t10-18:1 increased in RBC and plasma (P < 0.05). By 76 d, proportions of t10-18:1 declined in both RBC and plasma to 0 d levels. RBC and plasma t-18:1 compositions were highly correlated for all time points and overall (R≥0.7, P ≤ 0.02). Correlations with post slaughter backfat were, however, consistently greater for RBC compared to plasma. The use of RBC t-18:1 composition may, therefore, be superior for predicting t-18:1 composition in other tissues, and the length of finishing on barley could be useful for manipulating the composition and content of t18:1 in beef.